Canada Chair in hypertension prevention and control: A pilot project - Campbell, Norm RC (Pulsus Group Inc, 2007)
A five-year pilot project was initiated in Canada to fund an individual to lead the effort in improving hypertension prevention and control. As the initial recipient of the funding, the author’s objectives were to provide leadership to improve the management of hypertension through enhancements to the Canadian Hypertension Education Program, to increase public knowledge of hypertension, to reduce the prevalence of hypertension by reducing dietary sodium additives and to develop a comprehensive hypertension surveillance program. The initiative has received strong support from the hypertension community, the Public Health Agency of Canada, the Heart and Stroke Foundation of Canada, and many Canadian health care professional and scientific organizations. Progress has been made on all objectives. The pilot project was funded by The Canadian Hypertension Society, the Canadian Institutes of Health Research and sanofi-aventis, in partnership with Blood Pressure Canada, and will finish in July 2011.